2020
DOI: 10.1111/all.14157
|View full text |Cite
|
Sign up to set email alerts
|

CARsomes inhibit airway allergic inflammation in mice by inducing antigen‐specific Th2 cell apoptosis

Abstract: Background: Skewed T helper (Th)2 response plays a crucial role in the pathogenesis of allergic diseases. The therapeutic efficacy for allergic diseases is unsatisfactory currently. This study aims to regulate the skewed Th2 response with CARsomes. Methods: The CARsome consisted of an epitope of Dermatophagoides farina-1 (Derf1), a segment of the anti-DEC205 antibody, the scFv, and an open reading frame of perforin. This fusion protein binds to DEC205 molecule on the surface of exosomes derived from dendritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It may represent a therapeutic modality for severe cases, if its mechanisms are better understood. The apoptotic process of lymphocytes can be regulated in the cell by exogenous and/or intrinsic factors and can be modulated with the role of pro‐ and anti‐apoptotic molecules 49,50 . Lymphopenia has been found in SARS and MERS, which were reported to induce apoptosis in the liver, lung, and T lymphocytes 51 .…”
Section: Lymphopenia In T Cellsmentioning
confidence: 99%
“…It may represent a therapeutic modality for severe cases, if its mechanisms are better understood. The apoptotic process of lymphocytes can be regulated in the cell by exogenous and/or intrinsic factors and can be modulated with the role of pro‐ and anti‐apoptotic molecules 49,50 . Lymphopenia has been found in SARS and MERS, which were reported to induce apoptosis in the liver, lung, and T lymphocytes 51 .…”
Section: Lymphopenia In T Cellsmentioning
confidence: 99%
“…After intranasal administration of MSCs-Exo, the decrease in IgE, OVA-IgE, and histamine levels relieved the classic symptoms; the decrease in CCL-11 levels is linked to lower eosinophil in ltration; the change in ICAM-1 and Th2 cytokine levels is linked to reduced in ammation; and increased IFN-γ levels can stimulate the expression of IgG2a and inhibit the production of IgG3, IgG1, IgG2b, and IgE 29 , thus further exerting a therapeutic effect on AR. Many studies have also demonstrated that after intravenous treatment with different kinds of exosomes in an asthma mouse model, in ammation of lung tissues decreased, and Th2 cytokine and in ammatory cytokine levels were lower in serum and BALF [30][31][32] . All these results imply that intranasal delivery of MSCs-Exo has an effect similar to that of intravenous delivery to suppress allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…This has been explored through the development of EVs decorated with chimeric antigen receptors (CARsomes). CARsomes derived from dendritic cells were shown to induce apoptosis in antigen-specific T helper 2 (T h 2) cells and may be able to attenuate allergic airway inflammation [ 129 ]. Notably, T h 2 cells are thought to be drivers of the pathology seen in allergic asthma.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%